2004
DOI: 10.1021/ja039577h
|View full text |Cite
|
Sign up to set email alerts
|

CO2 Fixation by Copper(II) Complexes of a Terpyridinophane Aza Receptor

Abstract: CO2 is fixed by a Cu2+ complex of a macrocyclic terpyridinophane ligand forming a carbamate group. Several features of the structure mimic the enzyme rubisco.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
52
0
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(54 citation statements)
references
References 12 publications
1
52
0
1
Order By: Relevance
“…This feature, the formation of a carbamate from atmospheric carbon dioxide and its stabilization, has been reproduced by an artificial model (Figure 27.28) [101].…”
Section: Unnatural Enzyme Models J2301mentioning
confidence: 71%
“…This feature, the formation of a carbamate from atmospheric carbon dioxide and its stabilization, has been reproduced by an artificial model (Figure 27.28) [101].…”
Section: Unnatural Enzyme Models J2301mentioning
confidence: 71%
“…According to previous reports, some copper complexes could separate and fix CO 2 under mild conditions . Our previous work has also shown that dinuclear copper(II) cryptate could easily take up atmospheric CO 2 and convert it into carbonate monoesters in alcohol solution .…”
Section: Figurementioning
confidence: 75%
“…The most important conclusion of these reports is that, for systems where the coordination of CO 2 is not reversible, the ability to transform CO 2 into other compounds depends on the extent of the charge transfer from the transition metal to CO 2 . If the metal transfers an electron, the formation of C-C bonds is possible and the rigidity of the bimetallic system seems to play an essential role in the formation of this bond [13,14]. In this sense, interestingly, one of the most innovative works in the area of CO 2 reduction reported by Angamuthu et al in 2010 consists in the synthesis of a tetranuclear complex of Cu(I) with the ligand N-(2-mercaptopropyl)-N,N-bis(2-pyridylmethyl)amine, which spontaneously and selectively captures CO 2 from the air [15].…”
Section: Introductionmentioning
confidence: 99%